Educational Resource Management System Design for Inclusive Education - Sari, Rahayu Widiya; Purba, Arista; Nasution, Saharni; Pulungan, Lilik Hidayat (Lembaga Riset Mutiara Akbar, 2024)
The research aims to describe the design of an optimal education resource management system to support inclusive education. Inclusive education recognizes the right of every child to quality education, regardless of their special needs. Effective education management is needed to ensure the successful implementation of inclusive education programs in elementary schools. Using a comprehensive literature study method, this research analyzes relevant literature to understand the concept of inclusive education management, the role of the principal, and the challenges and models of its implementation. The results show that effective educational management, supported by the strong leadership role of the principal, is very important in creating an inclusive learning environment and supporting the success of all students, including those with special needs.